Corneal confocal microscopy to detect early immune‐mediated small nerve fibre loss in AL amyloidosis. Issue 6 (30th April 2022) - Thimm, Andreas; Carpinteiro, Alexander; Oubari, Sara; Papathanasiou, Maria; Kessler, Lukas; Rischpler, Christoph; Malik, Rayaz Ahmed; Reinhardt, Hans Christian; Rassaf, Tienush; Herrmann, Ken; Kleinschnitz, Christoph; Stettner, Mark; et al.
Abstract: Objective: Light chain (AL) amyloidosis is a life‐threatening disorder characterised by extracellular deposition of amyloid leading to dysfunction of multiple organs. Peripheral nerve involvement, particularly small fibre neuropathy, may be associated with poorer survival. Corneal confocal microscopy (CCM) is a rapid and non‐invasive imaging technique to quantify corneal small nerve fibres and immune cells in vivo. We aimed to evaluate CCM as a tool for early diagnosis of peripheral nerve involvement in AL amyloidosis. Methods: CCM and nerve conduction studies (NCS) were undertaken in 21 newly diagnosed, treatment‐naïve AL amyloidosis patients and 21 age‐ and sex‐matched healthy controls. Corneal nerve fibre density (CNFD), corneal nerve branch density and fibre length, and cell infiltrates were quantified in the sub‐basal layer of the cornea. Results: There was a significant reduction in CNFD and nerve fibre length, even without large fibre affection and an increase in cell density, particularly around corneal nerve fibres in patients with AL amyloidosis compared to controls. Additionally, cell infiltration correlated with reduced nerve fibre density in patients with AL amyloidosis, but reduced CNFD did not correlate with laboratory parameters of organ dysfunction. Interpretation: Our study is the first to show that CCM allows rapid non‐invasive identification of early small nerve fibre damage associated with immune cell infiltration in patients with AL amyloidosis. CCM detects peripheral nerve involvement more sensitively than NCS.